DECISION MAKING ANALYSIS IN SELECTING THE SUSTAINABILITY OF PT ANEKA TAMBANG PONGKOR MINE USING ANALYTICAL HIERARCHY PROCESS (AHP) - Zafar Nur Hakim, Mokhamad
PT Aneka Tambang Tbk. (ANTAM) was a state owned company that has several business segments namely nickel, bauxite, and gold. Pongkor Gold Mine is one of ANTAM's business units engaged in gold commodities. Operating since 1994, gold reserves in Pongkor are running low. With the mining permit (Izin Usaha Pertambangan) which will expire soon in 2021, the management of PT ANTAM UBP (Unit Bisnis Pertambangan) Emas Pongkor must immediately make a decision regarding the sustainability of the business unit. This Final Project would like to evaluate what is the best decision for PT ANTAM UBP Emas Pongkor using two methods, namely quantitative using cost-benefit analysis, and qualitative method using Analytical Hierarchy Process (AHP). In this research, three most feasible alternatives have been determined, namely mine closure, continue normal, and continue with improvisation. AHP can also show which criteria have the most influence in the decision making process. In determining the criteria and sub-criteria that affect the decision making process, this study uses the triple bottom line concept (Elkington, 2018) which is synchronized with the company's vision and mission. The result of evaluation showed that there are four main criteria that affect the decision making process, namely profit, social, employment, and the environment. And the sub-criteria are company profit, country income, social economic, security assets, jobholder and labor supply. The results show that overall, the company profit sub-criteria most influence the decision-making process, with a global priority value of 27.3%. Then followed by the environment with a value of 19.7%, and the jobholder sub-criteria with a value of 17.7%. From the cost-benefit analysis, continuing the mine by applying improvisation in several parts has the greatest benefit value for 5 (five) years, with total value of Rp467,027,000,000. Meanwhile, if the decision taken is to continue mining production under normal conditions, it will give a total value of Rp335,797,000,000. And if the decision taken is mine closure, it will give a total value of Rp(-25,205,000,000). This is also supported by the results of AHP data analysis. From 13 respondents, 9 of them chose Continue with Improvisation as the best decision for the sustainability of the Pongkor Mine. From the group result, global priority values for each alternative are 55% for continue improvised, 30.3% for continue normal, and 14.8% for mine closure. So the group result of 13 respondents concluded that continue with improvisation is the best choice with the highest value of global priorities. After getting the best alternative, the next is to implement the improvisation. Those improvisations are reduction in labor costs and SGA costs. In reducing labor costs, there are several efforts that companies can make, including the early retirement program, the employee rotation program, and the centralization program. Meanwhile, to reduce the impact of reducing SGA costs, several negotiation efforts with several parties are also required.